Reconfiguring Digital Practices: Habitus, Capital, and the Second-Account Field among Generation Z - Amelia, Putri; Hidayat, Medhy Aginta (Universitas Wijaya Kusuma Surabaya, 2026)
This study examines how digital practices are reconfigured through the use of second Instagram accounts among Generation Z, focusing on the interplay of habitus, capital, and field. The phenomenon of second-account usage reflects not only a strategy of identity negotiation, but also a structured response to the pressures of visibility, self-presentation, and symbolic evaluation within the main account. Grounded in Pierre Bourdieu’s theory of social practice, this research employs a qualitative phenomenological approach. Data were collected through semi-structured interviews, non-participant observation, and documentation, enabling an in-depth understanding of the lived experiences of Gen Z users. The findings show that digital habitus, formed through family environments, peer interactions, and routine engagement with social media, shapes how users perceive and navigate online spaces. Cultural capital, in the form of digital competence, and social capital, particularly strong and selective networks, are strategically mobilized to manage visibility and control access. The study further reveals that second accounts constitute a differentiated digital field, where the dominant logic of symbolic capital in the main account is partially reconfigured. Within this space, users negotiate power, redefine value, and develop practices that prioritize intimacy, trust, and controlled self-expression.